Microclimate influence investigation on broilers industrial production intensification by information technology methods - Belykh, T I; Burdukovskaya, A V; Ivonina, O Y; Arkhipova, Z V (IOP conference series. Earth and environmental science, 2021)
The article contains regression mathematical models that describe the effect of mechanical and automatic microclimate control systems on the growth and development of Arbor Acres broiler chickens in Sayan broiler agro-industrial complex in conditions of on-ground keeping. The following microclimate parameters are considered: temperature, humidity, illumination. Cramer-Welch, Wilcoxon criteria are used to test the statistical hypothesis of homogeneity of the two considered samples. The Chow test is taken on the possibility of constructing two different mathematical models of the same type that describe the patterns of development of simulated indicators. Statistical estimates of the significance of the constructed models and factors included in the models are calculated. The Fisher criterion is checked to see the differences in the constructed models and choose a more acceptable one to describe the effect of the microclimate on the production of young birds. The results of regression analysis are interpreted in relation to the subject area under study. Graphical visualization of analysis of initial and output data of built models is performed. Factors are ranked by degree of their effect on the resulting index using elasticity coefficients and share of their influence. The main production indicators are calculated according to the results of population cultivation - average daily growth, absolute growth, relative growth rate, liveability. The article calculates the economic effect in one complete cycle of broiler chickens growing.